Selecting Medicinal Plants for Development of Phytomedicine and Use in Primary Health Care - Barbosa, Wagner Luiz Ramos; Nascimento, Myrth Soares do; Pinto, Lucianna do Nascimento; Maia, Fernando Luiz Costa; Sousa, Antonio Jorge Ataíde; Júnior, José Otávio Carréra Silva; Monteiro, Maurícia Melo; Oliveira, Danilo Ribeiro de (IntechOpen, 2012)
None